Robert A. Taft papers - Taft, Robert A. (Robert Alphonso), 1889-1953.
Correspondence, speeches, writings, political and legislative files, subject files, business and financial records, family papers, and other papers relating primarily to Taft's career as a U.S. senator and to his role as a national leader in the Republican Party. Subjects include public policy and legislative issues especially in the areas of defense, economic policy, education, finance, foreign policy, labor, public housing, taxation, and veterans' affairs. Topics include his Cincinnati law practice, World War I service, national and Ohio state politics, political campaigns between 1938 and 1952, and Yale University. Family members represented include Taft's parents, Helen Herron Taft and William H. Taft; his sister, Helen Taft Manning; his wife, Martha Wheaton Bowers Taft; and his son, Robert Taft.
Individuals represented by correspondence or subject matter are John W. Bricker, Forrest Davis, Thomas E. Dewey, Everett McKinley Dirksen, Dwight D. Eisenhower, John B. Hollister, Herbert Hoover, David S. Ingalls, Julius Klein, David Eli Lilienthal, Douglas MacArthur, Henry F. Pringle, Franklin D. Roosevelt, Harold E. Stassen, Adlai E. Stevenson, Harry S. Truman, and Wendell L. Willkie.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. senator from Ohio, Republican Party leader, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bricker, John W. -- 1893-1986.; Davis, Forrest, -- 1893-1962.; Dewey, Thomas E. -- 1902-1971.; Dirksen, Everett McKinley; Eisenhower, Dwight D. -- 1890-1969.; Hollister, John B. -- 1890-1978.; Hoover, Herbert, -- 1874-1964.; Ingalls, David S. -- 1899-; Klein, Julius, -- 1901-1984.; Lilienthal, David Eli, -- 1899-1981.; MacArthur, Douglas, -- 1880-1964.; Manning, Helen Taft, -- 1891-1987.; Pringle, Henry F. -- 1897-1958.; Roosevelt, Franklin D. -- 1882-1945.; Stassen, Harold Edward, -- 1907-2001.; Stevenson, Adlai E. -- 1900-1965.; Taft, Helen Herron, -- 1861-1943.; Taft, Martha Wheaton Bowers, -- -1958.; Taft, Robert, -- 1917-1993.; Taft, William H. -- 1857-1930.; Truman, Harry S., -- 1884-1972.; Willkie, Wendell L. -- 1892-1944.; Taft family; United States. -- Congress. -- Senate; Republican Party (U.S. : 1854- ); Yale University; Education -- United States; Elections -- United States; Labor -- United States; Practice of law -- Ohio -- Cincinnati; Public housing -- United States; Taxation -- United States; Veterans -- United States; World War, 1914-1918.; Ohio -- Politics and government; United States -- Defenses; United States -- Economic policy -- 20th century; United States -- Foreign relations -- 20th century; United States -- Politics and government -- 1901-1953.; Lawyers; Politicians; Senators, U.S. Congress -- Ohio